2005
DOI: 10.1051/0004-6361:20047042
|View full text |Cite
|
Sign up to set email alerts
|

Thick disks and halos of spiral galaxies M 81, NGC 55 and NGC 300

Abstract: Abstract. By using images from the HST/WFPC2/ACS archive, we have analyzed the spatial distribution of the AGB and RGB stars along the galactocentric radius of nearby spiral galaxies M 81, NGC 300 and NGC 55. Examining color-magnitude diagrams and stellar luminosity functions, we gauge the stellar contents of the surroundings of the three galaxies. The red giant population (RGB) identified at large galactocentric radii yields a distance of 3.85 ± 0.08 Mpc for M 81, 2.12 ± 0.10 Mpc for NGC 55, and 2.00± 0.13 Mp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
57
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 86 publications
16
57
2
Order By: Relevance
“…As a result, the model adopting an inside-out formation scenario (i.e., τ = 0.35r/r d + 2.47 Gyr) and an appropriate gas outflow rate (i.e., b out = 0.9) can successfully reproduce the observed constraints of NGC 300. Our results suggest that NGC 300 likely experiences a rapid growth of its disk and its stellar population is predominately old, consistent with the previous observed results (Butler et al 2004;Tikhonov et al 2005;Gogarten et al 2010).…”
Section: Discussionsupporting
confidence: 92%
“…As a result, the model adopting an inside-out formation scenario (i.e., τ = 0.35r/r d + 2.47 Gyr) and an appropriate gas outflow rate (i.e., b out = 0.9) can successfully reproduce the observed constraints of NGC 300. Our results suggest that NGC 300 likely experiences a rapid growth of its disk and its stellar population is predominately old, consistent with the previous observed results (Butler et al 2004;Tikhonov et al 2005;Gogarten et al 2010).…”
Section: Discussionsupporting
confidence: 92%
“…The ACS field is located somewhat beyond the WFPC2 field of Mouhcine et al (2005), which is also shown. The ellipse indicates the 22 (∼25 kpc) extent of M81's thick disk as suggested by Tikhonov et al (2005), inclined at 59 • . The box at the upper center is the location of the deep ACS study by Williams et al (2009) and Dalcanton et al (2009).…”
Section: Introductionmentioning
confidence: 92%
“…The specific pointing was chosen to lie along the southwestern semi-minor axis, beyond the radius suggested as the edge of M81's thick disk (Tikhonov et al 2005), where the surface brightness of M81 is still high enough that we can determine a meaningful metallicity distribution from RGB stars. The left panel of Figure 1 shows the location of our ACS pointing.…”
Section: Observations and Reductionsmentioning
confidence: 99%
“…Ever since the existence of a thick disk component was shown by star counts in the Milky Way (Gilmore & Reid 1983) and by stellar luminosity distribution studies of external early-and late-type galaxies (Burstein 1979;Tsikoudi 1979;van der Kruit & Searle 1981a;Shaw & Gilmore 1989;Dalcanton & Bernstein 2002;Pohlen et al 2004;Tikhonov et al 2005), its origin and properties have been the subject of a continuing vigorous debate. The distinctive properties of their stars, e.g.…”
Section: Introductionmentioning
confidence: 99%